The Use of Taro Flour (Colocasia esculenta (L.) Schott) As Ingredient Substitution of Wheat Flour In Making Cookies - Fuadini Therik; Sri Anna Marliyati; Lilik Noor Yuliati (Media Gizi dan Keluarga, 2001)
The objective of this research are to know the best level substitution of wheat flour by taro flour in making cookies, to know the nutrient contain of cookies and consumer acceptability of cookies had substitution by taro flour. Substitution of taro flour were 0%, 10%, 20% and 30%. The result of this research showed that taro flour contained moisture 5,72%, ash 2,24%, fat 2,01%, protein 3,90%, carbohydrate 91,70%, crude fibre 2,70% and calorie 400,91 Kal. The cookies contained moisture 2,93-3,38%, ash 1,53-1,83%, fat 35,37-39,87%, protein 6,35-7,28%, crude fibre 0,66-1,15%, carbohydrate 51,44-55,92% and calorie 570,81-593,24 Kal. The panellist like the cookies produced and the best level substitution is 20%.